Pemberdayaan Kelompok Perempuan dalam Akses Layanan Publik Digital: Menuju Kemandirian Administrasi Desa - Nur Aini Mayasiana; Adinda Atika Pratiwi; Siska Putri Aprilia; Danira Maria Rosari Oktavita; Aklima Zikra (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
The digital transformation of village public services requires the readiness of all community groups, including rural women who play a strategic role in village administration and public services. However, limited digital literacy has hindered women’s groups from independently accessing digital public services. This community service activity aims to enhance the capacity of women’s groups in accessing digital public services to support administrative independence in Suci Village, Panti Sub-district. The implementation methods include socialization, digital literacy training, assistance in using village digital public services, and activity evaluation. The target participants are women’s groups actively involved in community and village administrative activities. The results indicate improved understanding and skills among women’s groups in accessing digital public services, as well as increased women’s participation in village administrative processes. This community service contributes to strengthening village administrative independence and promoting more inclusive digital public services.